Effects of COVID-19 pandemic on provision and use of maternal health services in Allada, southern Benin: a local health system perspective - Akpi, Éric; Vigan, Armelle; Boyi Hounsou, Christelle; Gandaho, Marlène; Houngbo, Gisèle; Gryseels, Charlotte; Dossou, Jean-Paul; Delvaux, Thérèse (Frontiers in Public Health, 2023)
Objective: To assess the effects of the COVID-19 pandemic on the provision and use of maternal health services in southern Benin from a local health system perspective. Methods: We conducted a qualitative study from April to December 2021 in a health district in the Southern of Benin. We interviewed health workers involved in antenatal, delivery, postnatal and family planning care provision, alternative and spiritual care providers, administrative staff of the district hospital, community health workers, adolescents and women who had given birth in the past six weeks in public health centers were interviewed. The World Health Organization health systems building blocks framework was used to guide the thematic analysis from a local health system perspective.The COVID-19 pandemic changed the lines of command and the institutional arrangements in the local health systems leadership; it put the interpersonal relationships in the health care provision team under stress and reduced the overall revenues of the district hospital. The motivation of allopathic health workers was undermined. Communities underutilized maternal health services in the COVID-19 period. Plausible causes included negative patient perceptions of COVID-19 measures taken at the public health facility level as well as well as fear of being forcibly vaccinated against COVID-19 in the health facilities.In times of health crises, appropriate local health system governance that integrates providers' concerns into effective guidelines is critical to reach and maintain a sufficient level of work motivation to ensure quality maternal health services.